PEMANFAATAN TEH KOMBUCHA SEBAGAI OBAT HIPERURISEMIA MELALUI PENURUNAN KADAR ASAM URAT DAN MALONDIALDEHID - Ni Luh Putu Kartika Mardiani; Ida Bagus Putra Manuaba; I Wayan Suirta (Jurnal Kimia (Journal of Chemistry), 2014)
Research has been conducted to determine the decrease in uric acid levels and malondialdehyde (MDA) of rats hyperuricemia after being given kombucha tea. The research was carried out with the draft post-test control group design. Kombucha tea with various fermentation time of 4, 8 and 12 days were given to hyperuricemia rats with doses of 10 mL/kg body weight and 40 mL/kg body weight. The results showed that kombucha tea can lower uric acid levels and MDA with the most significant decrease showed by the 8 day fermented kombucha tea with a dose of 40 mL/kg body weight. The decreases were 2.00±0.09 mg/dL and 1.68±0,34 umol/L respectively.